Non-toxigenic Corynebacterium diphtheriae in hallux ulceration - Gauthier Delvallez; Edgar Badell; Sokleaph Cheng; Soda Meng; Vivandet Tong; Judy Norman; Julie Toubiana; Koen Vandelannoote; Anne-Laure Bañuls; Mallorie Hide; Sylvain Brisse (Journal of Infection in Developing Countries)
Introduction: Toxigenic Corynebacterium diphtheriae causes classical diphtheria. Skin infections by toxigenic or non-toxigenic Corynebacterium diphtheriae are prevalent in the tropics but are rarely reported.